2019
DOI: 10.1080/23802359.2019.1618211
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Acer catalpifolium (Sapindaceae), a rare and endangered plant in Southwest China

Abstract: Acer catalpifolium is a rare and endangered species in southwestern China. In this study, the complete chloroplast genome sequence of A. catalpifolium was characterized by de novo assembly using highthroughput sequencing. The length of the whole chloroplast genome was 156,225 bp, containing a large single copy region (LSC) of 85,976 bp and a small single copy region (SSC) of 18,066 bp, which were separated by a pair of 26,092 bp inverted repeat regions (IRs). The sequence contained 135 unique genes, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A DNA sequencing study showed that A. catalpifolium is more closely related to Acer trees in the north of Sichuan Province (Wang et al, 2019). Compared with its deciduous broad-leaved relatives from the North, A. catalpifolium seems to be evolving to adapt to the warmer environment in Sichuan.…”
Section: Growth Habit and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA sequencing study showed that A. catalpifolium is more closely related to Acer trees in the north of Sichuan Province (Wang et al, 2019). Compared with its deciduous broad-leaved relatives from the North, A. catalpifolium seems to be evolving to adapt to the warmer environment in Sichuan.…”
Section: Growth Habit and Distributionmentioning
confidence: 99%
“…is a tree species native to China that is highly endangered. It belongs to the family Aceraceae and is closely related to Acer miaotaiense (Wang, He, Xu, Peng, & Zhao, 2019). At one time, it was believed that only 53 trees remained, and the species was listed in the “wild plants with extremely small populations (WPESP) rescue and protection plan” (State Forestry Administration of China, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…catalpifolium NC_041080.1 (Wang et al. 2019 ), Acer tataricum subsp. ginnala MN790641.1 (Yang et al.…”
mentioning
confidence: 99%